Benefits of Multilingualism in Foreign Language Learning: A Comparative Study of Bilingual and Multilingual Grammar Strategies - Emrah Dolgunsöz (Informascope, 2013)
In 21th century world in which the borders fade away, multilingualism and meeting multilingual individuals is quite a common phenomenon. This study aims to reveal any difference between multilingual and bilingual learners in constructing grammar strategies while learning English as L2 for bilinguals and L3 for multilinguals. It is hypothesized that multilinguals have superior grammar strategies when compared with bilinguals as they have linguistic knowledge for one more language. In this study, 3 groups of bilinguals (2 coordinate- additive bilingual groups and 1 balanced bilingual group) are compared with a group of multilinguals. Linguistic inventory for all bilingual groups include English and Turkish while it is French, Turkish and English for multilingual group. Current study is a quantitative one that includes a 33 item likert type questionnaire on grammar strategies by Kemp (2007). Cronbach Alpha coefficient of the study was calculated as .814 which indicated a high level of reliability. Data obtained from multilingual and bilingual groups were compared through Mann Whitney U Test and correlations are presented to reveal any difference. In the conclusion part, recommendations are given for instructors of multilingual and bilingual classes.